Sistem Aplikasi Teknologi Pemilu Digital - Sofyan Mufti Prasetiyo; Ahmad Suhendri; Muhammad Ikbal Ashara; Marsal Ibrahim; Hadi Suparman (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Election technology is a necessity in the digital era. The various conveniences offered by technology have encouraged many countries to use technology to help election administrators implement electoral democracy. Indonesia is a country that uses technology in elections. However, in practice, election technology does not necessarily produce efficiency and effectiveness. For example, the use of the SITUNG (Voice Counting System) application for the online-based vote recapitulation process has actually caused polemics in the community regarding public trust which was triggered by a technical error in the election organizers. This was exacerbated by the presence of negative issues and fake news during the election as a consequence of the post truth era. This article discusses the use of election technology in the vote recapitulation stage process through SITUNG in the 2019 election which presents a debate between efficiency and public trust. The results of the study show that the use of SITUNG in the vote recapitulation process is controversial because a technical error made by the election organizers in the data input process to SITUNG triggers public doubts and suspicions. This momentum was used by the candidates and political elites who lost the election to mobilize the masses to create public distrust which ultimately led to efforts to delegitimize the election results.